Cooperative control of power quality compensators in microgrids - Morales-Paredes, Helmo K. [UNESP]; Burgos-Mellado, Claudio; Bonaldo, Jakson Paulo; Rodrigues, Diego Tardivo [UNESP]; Quintero, Juan Sebastian Gomez (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper proposes a consensus-based distributed control scheme, augmented by the conservative power theory for compensating imbalance and harmonics at the Common Connection Point (PCC). The consensus algorithm allows to achieve effective coordination among the grid-following converters; whereas the conservative power theory is used to compute the unwanted currents and powers at the connection point that should be compensated via the remaining volt-ampere (VA) capacity of each converter. The mathematical formulation of the proposal, along with its validation through simulations, using a three phase - four wire microgrid, is provided.
Keywords: Consensus-based cooperative control; Control methods for electrical systems; Harmonic distortion; Load imbalance; Power quality; Smart grids